THE EFFECTIVENESS OF EAST JAVA ONLINE SHOPPING (JATIM BEJO) IN ENCOURAGING THE PARTICIPATION OF LOCAL MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - Irsanti, Nur Indah; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to evaluate the effectiveness of the East Java Online Shopping Program (JATIM BEJO) in encouraging the participation of local Micro, Small, and Medium Enterprises (MSMEs) as a response to the economic downturn caused by the Covid-19 pandemic. Method: A descriptive qualitative approach was applied, using Subagyo’s four indicators of effectiveness in Budiani (2007)—target accuracy, program socialization, goal achievement, and program monitoring—as the analytical framework. Results: The findings reveal that JATIM BEJO has succeeded in increasing MSME participation in digital platforms, thereby expanding market access and supporting economic resilience. However, challenges persist, including limited understanding among MSME actors regarding program benefits and administrative barriers that restrict broader participation. These issues highlight the need for more intensive socialization and technical assistance to ensure inclusive involvement. Novelty: This study contributes by emphasizing JATIM BEJO as a regional digital innovation that not only facilitates economic recovery but also provides a strategic model for empowering MSMEs in the post-pandemic era, underscoring the importance of adaptive policy design and continuous program evaluation for sustainable local economic development.